ANALYSIS OF THE IJAB QABUL IN THE SALE OF BEAN SPROUTS ACCORDING TO THE IMAM HANAFI’S PERSPECTIVE - Asri Maulidia; Sulfanwandi (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This paper analyzes the role of ijab qabul in the transaction of taoge (bean sprouts) from the perspective of Imam Hanafi. Ijab qabul is a crucial component in Islamic transactions necessitating a legitimate offer (ijab) and acceptance (qabul) between the seller and buyer. This research used a library study technique with a normative qualitative approach to investigate and analyze the implementation of ijab qabul in the sale and purchase of taoge in Banda Aceh, while comparing it to Islamic legal perspectives, specifically those of Imam Hanafi. The findings reveal that, per Imam Hanafi, a sale and purchase transaction is deemed lawful provided ijab and qabul are articulated clearly, occur simultaneously, and are free from compulsion. Should a disparity arise between the offer and acceptance, or if there is an extended wait, the transaction may be considered invalid. The clarity of the item being sold, in this instance, taoge, is essential to prevent injury or unfairness to either party. The study reveals that, despite transactions in traditional marketplaces generally being performed informally, the norms of Islamic law regarding ijab qabul are nonetheless adhered to by the parties involved in the transactions. This research underscores the need of implementing Imam Hanafi's fiqh principles in sales transactions to maintain justice and avert harm.